Application of TEOS Modular System on the Preservation of Andesite Type Rock - nahar cahyandaru; Esther von-Plehwe Leisen; Hans Leisen (Balai Konservasi Borobudur Magelang, 2021)
Andesite rock is commonly used as a heritage building in Southeast Asia, especially in Indonesia. However, the study on consolidation of andesite rock is still limited. This study aimed to evaluate the application effectiveness of TEOS-based material on the andesite type rock in heritage materials. TEOS was used as a modular system with andesite powder to form mortar. This andesite-TEOS mortar system was applied to conservation techniques, especially for gap and joint filling. TEOS modular system was successfully applied to the andesite type rock, resulting in chemical and physical properties. The color of the mortar and the compatibility with the original rock color were designed from the rock powder preparation. The excellent repair was obtained by a combination of dot technique gluing using epoxy resin and the TEOS mortar application in the gaps. Furthermore, this technique was successfully applied to the big Buddha Statue Head andesite rock for the emergency intervention of the falling fragment. Keyword: Andesite, Consolidation, TEOS, Mortar